The effect of video-assisted jigsaw learning on students' motivation and science learning outcomes - Rahayu, Sri; Annur, Saipul; Diki, Diki (Univeritas Papua, 2024)
This research aims to determine the effect of jigsaw learning assisted by video media on students' motivation and cognitive learning outcomes. This research uses an experimental design, which is one part of the quantitative method. Sampling for the experimental group and control group in this study used simple random sampling from all class V students in Gugus Melati, East OKU Buay Madang District, which consists of 5 state elementary schools. A total of 60 students were sampled, of which 30 were in the experimental class (SD Negeri 2 Tokorejo) and 30 were in the control class (SD Negeri Pengandonan). Data collection instruments use questionnaires and tests. Learning outcomes data were analyzed using the Mann-Whitney test and motivation using the t test. The results show that the students' initial abilities are the same (Sig. > 0.05), and after treatment they show differences (Sig. < 0.05). The motivation of experimental and control class students also has differences (Sig. < 0.05). The motivation and cognitive learning outcomes of students in the experimental class that used video-assisted jigsaw learning were better than those in the control class that used the lecture method. So it can be concluded that jigsaw learning assisted by video media has an effect on students' motivation and cognitive learning outcomes.